معالم الحسبة في الاجتماعات الأسرية: Hesba (al-Hisbah) milestones in family meeting - Abdul Karim Munshid Al-Dfairia, Dr Abdul Hamid (Online Journal of Research in Islamic Studies, 2023)
By nature, a man is a social being who interacts with the people around him, mainly if he interacts with his family members through their regular family gatherings. These interactions can be positive, such as being considerate, polite, and conducting good relationships, and they can be negative interactions, such as lying, backbiting, and gossiping. So, this study aims to identify the negative interactions that may occur in recurring family gatherings and dive into the negative aspects and ways to deal with them. This research method relies on historical, library and analytical approaches to reach results. Among the most important findings is hisba, an act to improve a person in the context of his interaction, and that hisba is also a way to deal with an individual’s behaviour with the members of his community, including during family gatherings where there is a lot of family social interaction. Then this paper also makes some recommendations, among which is the need for more studies in the field of family and issues related to hisba, the importance of finding a good solution that ensures Muslim families achieve domestic happiness, and the need to establish hisba in family meetings because of its capability of reforming individuals and society.